2020
DOI: 10.3171/2019.9.spine19954
|View full text |Cite
|
Sign up to set email alerts
|

A novel MRI-based score assessing trabecular bone quality to predict vertebral compression fractures in patients with spinal metastasis

Abstract: OBJECTIVEVertebral compression fractures (VCFs) in patients with spinal metastasis can lead to destabilization and often carry a high risk profile. It is therefore important to have tools that enable providers to predict the occurrence of new VCFs. The most widely used tool for bone quality assessment, dual-energy x-ray absorptiometry (DXA), is not often available at a patient’s initial presentation and has limited sensitivity. While the Spinal Instability Neoplastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 26 publications
3
38
0
Order By: Relevance
“…Using this technique, it has been shown that VBQ score correlates with BMD scores from DXA scans [8] and is an independent predictor of the occurrence of pathologic vertebral compression fracture in patients with spine metastasis. [9] This study expands these earlier findings by showing that VBQ score can predict fracture risk in patients without neoplastic disease. Although DXA remains the gold standard for osteoporosis screening due to its low cost and widespread ability, this study demonstrated that the predictive power of the VBQ score is independent of and greater than that of DXA BMD values.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Using this technique, it has been shown that VBQ score correlates with BMD scores from DXA scans [8] and is an independent predictor of the occurrence of pathologic vertebral compression fracture in patients with spine metastasis. [9] This study expands these earlier findings by showing that VBQ score can predict fracture risk in patients without neoplastic disease. Although DXA remains the gold standard for osteoporosis screening due to its low cost and widespread ability, this study demonstrated that the predictive power of the VBQ score is independent of and greater than that of DXA BMD values.…”
Section: Discussionsupporting
confidence: 81%
“…One recently described, novel technique for assessing bone quality is the vertebral bone quality (VBQ) score, which uses noncontrast, T1-weighted lumbar spine magnetic resonance imaging (MRI) [8]. The VBQ has been shown to both correlate with DXA-measured BMD scores [8] and predict vertebral compression fracture risk in patients with spine metastases [9]. By measuring T1-signal, VBQ estimates detrimental fat infiltration within the vertebral body, which is correlated with decreases in trabecular bone quality.…”
Section: Introductionmentioning
confidence: 99%
“…A new method of measuring bone quality (vertebral bone quality score) using magnetic resonance imaging has more recently been described since the initiation of this study and so was not able to be included. 29,30 Magnetic resonance imaging on cadavers in the biomechanics lab is also not likely to provide clinically accurate results, limiting future possibilities of investigating vertebral bone quality score in this type of study. 31…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy is commonly used for treatment of metastatic bone tumours, however in the movement towards localized control with stereotactic body radiotherapy (SBRT), the incidence of post treatment fractures has increased with post SBRT vertebral compression fractures occurring in approximately 11% of patients [3,[115][116][117][118]. As such, the focal impact of SBRT on bone quality [119][120][121] must be considered in the context of treatment planning and patient selection.…”
Section: Treatment Effectsmentioning
confidence: 99%